Von der Paneldiagnostik zu umfassenden genomischen Analysen - Leichsenring, Jonas; Kazdal, Daniel; Plöger, Carolin; Allgäuer, Michael; Endris, Volker; Volckmar, Anna-Lena; Neumann, Olaf; Kirchner, Matthias; Penzel, Roland; Rempel, Eugen; Budczies, Jan; Schirmacher, Peter; et al. (Der Pathologe, 2019)
Precision oncology is obtaining a central role in the therapy of malignant diseases. The indication for targeted therapy is based on the identification of molecular targets for which next-generation sequencing (NGS) is commonly used nowadays. All approved predictive biomarkers and molecular targets, including gene fusions and copy number alterations, can be identified depending on panel design and method applied. Some clinical scenarios, however, may require more holistic genomic approaches, such as whole-genome/whole-exome and transcriptome analysis, which must be embedded in a clinical trial. Here, key aspects and applications of each method are summarized and discussed.
Gesehen am 29.07.2019